Haemozoin Detection in Mouse Liver Histology Using Simple Polarized Light Microscope - DWI RAMADHANI; SITI NURHAYATI; TUR RAHARDJO (Bogor Agricultural University, Indonesia, 2014)
The presence of malarial pigment (haemozoin) due to Plasmodium infection is a common histopathological effect in mouse liver. Previous research showed that by using a polarized light microscope, researchers were better able to detect haemozoin in mouse liver histology section. Thus, the aim of this research was to compare the haemozoin area observed by a conventional vs. simple polarized light microscope by using image processing analysis. A total of 40 images produced from both conventional light microscope and simple polarized light microscope were collected. All images were analyzed using ImageJ 1.47 software to measure the haemozoin areas. Our results showed that non birefringent haemozoin and birefringent haemozoin area was significantly different. This was because when using conventional light microscope the brown area that contained images of non birefringent haemozoin images also contained Kupffer cells which appeared as the same brown color as haemozoin. In contrast, haemozoin gave bright effect and can be easily differentiated with Kupffer cells in the birefringent haemozoin images. This study concluded that haemozoin detection in mouse liver histology using a simple polarized light microscope was more accurate compared to that of conventional light microscope.